2017
DOI: 10.1007/jhep11(2017)065
|View full text |Cite
|
Sign up to set email alerts
|

The quantum Fokker-Planck equation of stochastic inflation

Abstract: Abstract:We derive the stochastic description of a massless, interacting scalar field in de Sitter space directly from the quantum theory. This is done by showing that the density matrix for the effective theory of the long wavelength fluctuations of the field obeys a quantum version of the Fokker-Planck equation. This equation has a simple connection with the standard Fokker-Planck equation of the classical stochastic theory, which can be generalised to any order in perturbation theory. We illustrate this for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 30 publications
(61 reference statements)
0
19
0
Order By: Relevance
“…Ref [39]. showed that time evolution of the density matrix in λφ 4 , corrected perturbatively at fixed O(λ)gives Fokker-Planck evolution for the diagonal entries.…”
mentioning
confidence: 99%
“…Ref [39]. showed that time evolution of the density matrix in λφ 4 , corrected perturbatively at fixed O(λ)gives Fokker-Planck evolution for the diagonal entries.…”
mentioning
confidence: 99%
“…This allows us to neglect deep-IR modes beyond the observable scales in calculating observable correlation functions. 2 Recently several papers appeared which try to extend Stochastic Formalism, in Schrödinger picture [24], or by using path integral method [25]. 3 This stochastic formalism is also called Starobinsky's stochastic formalism.…”
Section: Ir Secular Growth and Stochastic Formalismmentioning
confidence: 99%
“…The stochastic approach has been shown to reproduce the correct IR behaviour of the full QFT statistical propagator to leading order in the coupling [3,[17][18][19][20] and was recently favourably compared at two-loop order in perturbation theory [21]. Other authors have studied the evolution of the density matrix for the IR modes to recover a Fokker-Planck equation [22,23], and ref. [24] argued the emergence of the stochastic formalism from a leading-log diagrammatic analysis at coincident points.…”
Section: Introductionmentioning
confidence: 99%
“…[25,26] for example applications), and in recent years there has been an upsurge in activity aiming to extend it e.g. to beyond leading order in the coupling [22,27,28], the slow-roll approximation [16,29], or to include derivative interactions [30]. However, compared to its extensive use, studies of the embedding and range of validity of the stochastic approach in QFT remain scarce (see however [31,32]), which has motivated the present work.…”
Section: Introductionmentioning
confidence: 99%